Analisis Sistem Pemungutan PBB terhadap Optimalisas Penerimaan PAD Kecamatan Ciomas Kabupaten Bogor - Mochamad Fadhlan Fitryadi; Rahmat Mulyana Dali; Yudiana Yudiana (Journal on Education, 2023)
Regional governments now have control over the PBB-P2 tax on rural and urban land and buildings, which is a significant source of local revenue from the regional tax sector. In certain places, this has the potential to make a significant contribution to the local economy. Every year, Ciomas Regency has difficulty collecting taxes for various new reasons. Ciomas Regency learned from bitter experience that some residents are still not aware that they have to pay taxes. This will certainly lead to tax arrears and financial losses for Ciomas Regency. The implementation of PBB-P2 in Ciomas District shows a promising increasing trend from year to year. This research tries to investigate the optimization of PAD in Cio. Qualitative descriptive analysis, as well as optimization and contribution analysis, were used in this research. The realization of PBB income during this study has increased, but the level of effectiveness is still not ideal because it has not achieved the goals set by the regional government. The influence of PBB-P2 on PAD is quite large. The success of PBB-P2 can be increased by strengthening the data in the SPTPD and providing education to the public about the importance of taxes for development.